A modest proposal #London - 2018 - Hofman, Annelore; Ivanova, Victoria; Knowles, Caroline 1954-; Mason, Luke; Moreno, Louis; Phillips, Andrea; Rosamond, Emily (Jubilee vzw, 2018)
Vermeir & Heiremans' project, 'A Modest Proposal (in a Black Box)', investigates if financialisation can be repurposed as a tool to create more equitable conditions. The artists' proposal suggests that financialising public art collections, museum real estate and their symbolic capital could create a cycle of wealth that will benefit not only investors and institutions, but also the creators of these values, the original stake-holders?the artists and art workers.00'A Modest Proposal' aims to benefit artists and art workers, but its implementation raises some fundamental questions: can values originating from public goods be claimed for the benefit of specific stakeholders, or should the funds rather be redistributed through a political process? These pressing questions were addressed during the symposium for which Vermeir & Heiremans invited a number of speakers working in the fields of financial geography, art and law. The texts assembled in the present publication focus on the relationship between art and finance, the contemporary role of public museums and collections and the influence of financialisation on urban processes and daily life. The ultimate question the symposium wished to address is whether finance can be a useful tool to create a more equitable society. Exhibition: Pump House, London, UK (02.10.-16.12.2018)
Colophon: This artist book is published by Jubilee vzw on the occasion of "A Modest Proposal (Symposium)" which examined fundamental questions raised by Vermeir & Heiremans' exhibition "A Modest Proposal (in a Black Box)", presented at Pump House Gallery, London. - An Initial Public Exhibition curated by Ned McConnell for Pump House Gallery, London, from 2 October to 16 December 2018
A Modest Proposal symposium, 27 October 2018, Location: Gorvy Lecture Theatre, London
Keywords: Heiremans, Ronny -- 1962-; Schmuki, Salome -- 1979-; Vermeir, Katleen -- 1973-; Vermeir & Heiremans -- Künstlervereinigung; Pump House Gallery -- London; Geschichte 2018; Buchgestaltung; Kunstmarkt -- Motiv; Pumpwerk; Park; Video-Installation; Finanzierung; Restaurierung; Nutzungsänderung; Museumsbau; Politische Kunst; Konferenzschrift; Aufsatzsammlung; Künstlerbuch